Immunogenicity of COVID-19 booster vaccination in IEI patients and their one year clinical follow-up after start of the COVID-19 vaccination program - van Leeuwen, Leanne P. M.; Grobben, Marloes; GeurtsvanKessel, Corine H.; Ellerbroek, Pauline M.; de Bree, Godelieve J.; Potjewijd, Judith; Rutgers, Abraham; Jolink, Hetty; van de Veerdonk, Frank L.; van Gils, Marit J.; de Vries, Rory D.; Dalm, Virgil A. S. H.; et al. (Frontiers in Immunology, 2024)
Previous studies have demonstrated that the majority of patients with an inborn error of immunity (IEI) develop a spike (S)-specific IgG antibody and T-cell response after two doses of the mRNA-1273 COVID-19 vaccine, but little is known about the response to a booster vaccination. We studied the immune responses 8 weeks after booster vaccination with mRNAbased COVID-19 vaccines in 171 IEI patients. Moreover, we evaluated the clinical outcomes in these patients one year after the start of the Dutch COVID-19 vaccination campaign. Methods: This study was embedded in a large prospective multicenter study investigating the immunogenicity of COVID-19 mRNA-based vaccines in IEI (VACOPID study). Blood samples were taken from 244 participants 8 weeks after booster vaccination. These participants included 171 IEI patients (X-linked agammaglobulinemia (XLA;N=11), combined immunodeficiency (CID;N=4), common variable immunodeficiency (CVID;N=45), isolated or undefined antibody deficiencies (N=108) and phagocyte defects (N=3)) and 73 controls. SARS-CoV-2-specific IgG titers, neutralizing antibodies, and T-cell responses were evaluated. One year after the start of the COVID-19 vaccination program, 334 study participants (239 IEI patients and 95 controls) completed a questionnaire to supplement their clinical data focusing on SARS-CoV-2 infections. Results: After booster vaccination, S-specific IgG titers increased in all COVID-19 naive IEI cohorts and controls, when compared to titers at 6 months after the priming regimen. The foldincreases did not differ between controls and IEI cohorts. SARS-CoV-2-specific T-cell responses also increased equally in all cohorts after booster vaccination compared to 6 months after the priming regimen. Most SARS-CoV-2 infections during the study period occurred in the period when the Omicron variant had become dominant. The clinical course of these infections was mild, VNT virus neutralization test 98 XLA X-linked agammaglobulinemia